Coma Off It: Regularizing Variable Point-spread Functions - J. Marcus Hughes; Craig E. DeForest; Daniel B. Seaton (The Astronomical Journal, 2023)
We describe a rapid and direct method for regularizing, post facto, the point-spread function (PSF) of a telescope or other imaging instrument across its entire field of view (FOV). Imaging instruments in general blur point sources of light by local convolution with a PSF that varies slowly across the FOV, due to coma, spherical aberration, and similar effects. It is possible to regularize the PSF in post-processing, producing data with a homogeneous “effective PSF” across the entire FOV. In turn, the method enables seamless wide-field astronomical mosaics at higher resolution than would otherwise be achievable, and potentially changes the design trade space for telescopes, lenses, and other optical systems where data uniformity is important. For many kinds of optical aberration, simple and rapid convolution with a locally optimized “transfer PSF” produces extremely uniform imaging properties at low computational cost. PSF regularization does not require access to the instrument that obtained the data, and can be bootstrapped from existing data sets that include starfield images or other means of estimating the PSF across the field.